Respuesta :
Answer:
4(3 * 39 – 12) = 5(2 * 39 + 6)
x = 39
Step-by-step explanation:
4(3x – 12) = 5(2x + 6)
(12x - 48) = (10x + 30)
12x - 10x = 30 + 48
2x = 78
2x/2 = x
78/2 = 39
x = 39
No Prob :)
x=39 is the right answer. First you had to add by 48 from both sides of the equation. And it gave us, [tex]12x-48+48=10x+30+48[/tex]. Then simplify, and it gave us [tex]12x=10x+78[/tex]. Next, subtract by 10x from both sides of equation. And it gave us, [tex]12x-10x=10x+78-10x[/tex]. And then simplify, and it gave us, [tex]2x=78[/tex]. You can also divide by 2 from both sides of the equation. And it gave us, [tex]\frac{2x}{2}=\frac{78}{2}[/tex]. And finally, simplify and the answer is x=39 is the right answer. Hope this helps! Thank you for posting your question at here on brainly. And have a great day! -Charlie